1962
DOI: 10.1139/m62-061
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Rhizosphere Microflora of Citrus Trees: I. Quantitative Incidence of Microorganisms in Relation to Root and Shoot Growth

Abstract: For the purpose of examining the correlations, if any, between the root and shoot growths of three Citrus species and their rhizosphere microflora, studies were made with 6-year-old plants in the Annamalai University Experimental Orchard. The rhizosphere population was analyzed quantitatively. Bacteria were about 40 to 90 times, actinomycetes 2 to 6 times, and fungi 3 to 6 times more abundant in the rhizosphere than in the soil, in rhizosphere populations there was no significant difference between the three C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1962
1962
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…APPLIED [1,23]. Only a limited number of reports exist on the rhizosphere effect in long duration plants or trees [6,7,11,14,18,24]. The present study was carried out to examine the rhizosphere effect in ten ecologically as well as economically important trees of the Kumaun region of Indian Central Himalaya, covering an altitudinal range from 1200 m to 3610 m amsl (above mean sea level), representing subtropical, temperate and subalpine zones.…”
Section: Introductionmentioning
confidence: 99%
“…APPLIED [1,23]. Only a limited number of reports exist on the rhizosphere effect in long duration plants or trees [6,7,11,14,18,24]. The present study was carried out to examine the rhizosphere effect in ten ecologically as well as economically important trees of the Kumaun region of Indian Central Himalaya, covering an altitudinal range from 1200 m to 3610 m amsl (above mean sea level), representing subtropical, temperate and subalpine zones.…”
Section: Introductionmentioning
confidence: 99%
“…However, sulfur-oxidizing bacteria were absent in citrus rhizosphere (Rangaswami and Vasantharajan 1962b ) . There was no signi fi cant difference of rhizosphere microorganisms among the three Citrus species, though the fungal population in the rhizosphere of the citrus variety Pummelo was slightly higher than that in the other two varieties (Rangaswami and Vasantharajan 1962a ) . Additionally, aspergilli, penicillia, and gram-negative non-sporing rods were higher in rhizospheres than in soil, and Mucor, Rhizopus, gram-positive rods, cocci, and sporeformers less (Rangaswami and Vasantharajan 1962b, c ) .…”
Section: Rhizosphere Microbial Populationmentioning
confidence: 82%
“…Compared with the non-root soil, the bacteria, fungi, and actinomyces quantities of the citrus rhizospheres were 67.6, 12.4, and 26.9 times. However, another study conducted by Rangaswami and Vasantharajan ( 1962a ) showed that the fungi number was 3-6 times in the rhizospheres of the three 6-year-old citrus species in the Annamalai University Experimental Orchard than in soils, actinomycetes 2-6 times, and bacteria 40-90 times. However, sulfur-oxidizing bacteria were absent in citrus rhizosphere (Rangaswami and Vasantharajan 1962b ) .…”
Section: Rhizosphere Microbial Populationmentioning
confidence: 89%
“…C. grandis Osbeck (Pummelo), C. sinensis Osbeck (Sathgudi), and C. reticulata Blanco (Mandarin) a s well as control soil were collected as detailed in an earlier paper (12). Two types of roots, viz.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies with larger plants, especially orchard trees, are laclting. I n a previous paper (12) the authors reported on the quantitative incidence of microorganisms in the rhizosphere of three species of Citrus and their relation to root and shoot growths. T h e relative incidences of different morphological, physiological, and nutritional groups of bacteria in the rhizosphere are presented in this paper.…”
Section: Introductionmentioning
confidence: 99%